PERAN ADVOKAT SEBAGAI PELAKSANAAN MEDIATOR DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA PEKANBARU - Anugeraha, Rendra; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The role of an advocate in mediation in the Religious Court of Class 1.A Pekanbaru does not exist, at the time of mediation lawyers were not included in the mediation room to provide solutions for the achievement of mediation, in which case the advocate was also included in one of the law enforcement agencies, which was stated in Article 5 paragraph (1) Law No. 18 of 2003 concerning Advocates. And advocates also have the right to assist their clients both in the courtroom and outside the court as long as they are in the case. This is stated in a special power of attorney between the advocate as the legal service provider and the client as the recipient of legal services. This study uses a sociological juridical approach.Juridical sociological research or empirical research is an approach by looking in terms of the realities that occur in the field. While the nature of research is descriptive which aims to provide a clear picture of the problem being examined. The advocate's role in the implementation of mediators in the divorce case at the Pekanbaru Religious Court based on the laws and regulations which form the basis for the resolution of cases in the Religious Courts, formulating the principle of peace in the settlement of divorce cases. In this case the subject of the family is marriage. While one who can decide is divorce, then if the peace rule in the family law is included together with the settlement in the divorce case examination, this shows that peace is the best solution for all disputes resolved through the Religious Courts in accordance with their authority.Obstacles and constraints of advocates on the implementation of mediators in divorce cases at the Pekanbaru Religious Court, namely a. lack of socialization for parties, b. existence of a third party, c. Good faith from the parties is also one of the factors that determines the success of mediation in court, d. the absence of one party, often the litigant party is not present at the hearing even though he has been summoned appropriately twice in a row, this is what automatically causes mediation to fail and the case must be continued by the panel of judges.Keywords: Advocates' Role as Mediator Implementation